The Corner Of The Women In Medellín, Colombia: The Social Construction Of Space - Ochoa Sierra, María; Toro Jiménez, Juliana (Universidad Pedagógica y Tecnológica de Colombia, 2018)
This paper aims to reflect on the space as a social construction, based on the case of the Women's Corner, the result of a Municipal Agreement that sought recognition of women in the city and the generation of a meeting place for women's organizations. This analysis is made from an ethnographic exercise; the information generation techniques were immersion in the field, participant observation, field logging and semi-structured interview, and in turn, documentary research and a survey applied to a significant and unrepresentative sample, such as control mechanism.